Appraising cervical mucus: a new approach to evaluating contraceptives - Han, Leo; Padua, Emily; Edelman, Alison; Jensen, Jeffrey T. (The European journal of contraception & reproductive health care, 2018)
Purpose: Timing of sample collection represents a major source of variability in studies evaluating the effects of administered agents on cervical mucus in naturally-cycling women. We sought to create and validate an artificial model of the cervical mucus cycle using exogenous E2 and P4 replacement in ovarian suppressed women. Materials and methods: We conducted a prospective experiment (clinicaltrials.gov, NCT02969590) examining cervical mucus changes in six women during natural and artificial menstrual cycles [leuprolide acetate, estradiol transdermal patch (0.05-0.3 mg/day) and progesterone 200 mg/day]. We collected serum and mucus samples at each visit corresponding to early, mid and late follicular, ovulation and mid-luteal time points in the natural and artificial cycles. We evaluated mucus according to the modified Insler score described in the WHO laboratory Manual for the Examination and Processing of Human Semen. Results: We enrolled healthy women between 27 and 40 years of age. All of the subjects achieved a mucus score of ≥10 both in the natural cycle and during peak estradiol replacement levels (0.3 mg/day) in the artificial cycle. During the simulated luteal phase, all mucus scores were ≤5 (median 3.5; range 1-5), similar to scores seen in the luteal phase of natural cycles (median 1; range 1-3). Conclusions: Our artificial cycle model (leuprolide acetate suppression) and dose escalation with estradiol patches produced favourable cervical mucus with mucus scores similar to those in the periovulatory phase of natural menstrual cycles. Additional studies are needed to validate the model for evaluation of mucus effects of contraceptive agents.